Analysis of Online Gambling and Family Resilience Strategies in the Perspective of Islamic Family Law - Adang Djumhur Salikin (Jurnal Legisci, 2025)
Background. This article examines in depth the phenomenon of online gambling (al-qimār al-ʾiliktrūnī) as a systemic threat to the resilience of Muslim families, as well as formulates a resilience strategy framework based on Islamic Family Law (al-ahwāl al-shakhṣiyyah). Method. Using descriptive-analytical qualitative research methods and Islamic jurisprudence (fiqh) approaches oriented to maqāṣid al-sharīʿah (especially ḥifẓ al-māl, al-nasl, wa al-ʿaql), this study conducts a critical examination of the qaṭʿī (definite) postulates that prohibit gambling and its destructive impact on the family structure. Result. The findings of the study show that online gambling paralyzes the main pillars of the Islamic family: qiwāmah (leadership), nafaqah (nafkah), and tarbiyah (education). In response, this article offers a multi-layered model of resilience strategies that include preventive (al-wiqāyah), curative (al-ʿilāj), and restorative (al-iʿādah) aspects that are sourced from the internal mechanisms of the family (shūrā, muhāsabah), communal intervention (taḥkīm), to final legal protection (fasakh). Conclusion. The conclusion of the article emphasizes that the resilience of Muslim families in the digital era can only be built by consistently implementing sharia values comprehensively in family life, supported by a collective awareness of the dangers of online gambling.